Analysis of microbial flora diversity of leek red sour soup in Guizhou based on Illumina Miseq high-throughput sequencing - ZHOU Luona, LIU Hui, WANG Mei, LU Bangfu, LI Jun, LIU Junlin, CHEN Zhongai (Zhongguo niangzao)
The microbial diversity and community structure of red sour soup and leek red sour soup were analyzed by Illumina miseq high-throughput sequencing. The results showed that the bacterial flora relative abundance of leek red acid soup was higher than that of red acid soup, the diversity was lower than that of red acid soup, and the fungal flora was opposite. There were some differences in the microbial communities of the two kinds of red acid soup samples, which were mainly reflected in the relative abundance. A total of 8 bacterial phylum and 4 fungal phylum were annotated from red acid soup samples, a total of 18 bacterial phyla and 3 fungal phyla were annotated from leek red sour soup samples. The dominant bacterial phyla (relative abundance>1%) were all Firmicutes, Proteobacteria and Cyanobacteria, the dominant fungal phyla were all Ascomycota and Basidiomycota. A total of 43 bacterial genera and 25 fungal genera were annotated from the red sour soup samples, and 103 bacterial genera and 18 fungal genera were annotated from the leek red sour soup samples. The dominant bacterial genera (relative abundance>1%) were all Lactobacillus, Lentilactobacillus, Pediococcus, Kosakonia, Lacticaseibacillus and Lactiplantibacillus. The dominant fungi genera were all Saccharomyces, Amphinema, Pichia, Ascomycota_ gen_Incertae_sedis, Tetracladium and Kazachstania.